Analysis of pre-injury training load in middle distance athletics: A case study - Cardozo, Luis A.; Valencia Lara, María; Guerrero Jiménez, Julián; Borja Villamil, Sergio; Reina-Monroy, Javier L. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
Sports trainers have a wide variety of instruments and methods to control training to identify the level of internal or external load experienced by the athlete to avoid an injury. The objective of this study was to explore the training load middle-distance athletes prior to a sports injury that resulted in the temporary suspension of training. The semi-structured interview technique was used in the retrospective phase to inquire about the means and methods used for load control. In the prospective phase, the recording of the mean heart rate (HRm), Session Rating of Exertion Perception (sRPE), Monotony Index (MI), Fatigue Index (FI), Hydration levels by urine color and Epworth Sleepiness Scale were used. The results indicate that the sports injury occurred prior to several high intensity sessions expressed in sRPE and in the week of higher volume, with this situation not being reflected through the FCm, nor in the week of higher value in IM and IF. Additionally, with levels of dehydration and an increase in the somnolence scale being evidenced in the last weeks of training. It is concluded that some methods to control training load do not reflect the real load experienced by the athlete, therefore, it is important to implement various mechanisms to reduce the risk of injury.